THE MODERN SYSTEM OF NON-MATERIAL STIMULATION OF PERSONNEL OF THE ORGANIZATION - A. Mitrofanovа (Вестник университета, 2016)
The most important condition of increase of efficiency of activity of companies is staff incentives. And if financial incentives are investigated well enough, the question of non-material motivation of staff requires further study. This problem devoted this article. The author paid special attention to the areas of non-financial incentives as awareness and promotion of free time. The results of the analysis of domestic and foreign experience of non-material incentives of personnel. Specific recommendations on the organization of flexible work schedules of employees, and to develop a corporate portal for employees with the aim of increasing awareness and involvement of staff in the management of the company.